Mood Matters From Rising Skirt Lengths to the Collapse of World Powers - Casti, John L.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Mood Matters" makes the radical assertion that all social events ranging from fashions in music and art to the rise and fall of civilizations are biased by the attitudes a society holds toward the future. When the "social mood" is positive and people look forward to the future, events of an entirely different character tend to occur than when society is pessimistic. The book presents many examples from every walk of life in support of this argument. In addition, methods are given to actually measure the social mood and to project it into the future in order to forecast what$1 (Bs likely or not over varying periods of time. Casti's writing is a pleasure to read and its contents an eye-opener. "They [the chapters] tell an engrossing story, and the mystery heightens as it goes. . . . it's chatty and knowing." Greg Benford, Physicist and science-fiction writer, author of "Timescape" and "Deep Time" "I am struck by how thought-provoking it all is. I am sure that your book will draw a lot of attention" Tor Norretranders, Science writer, author of "The Generous Man" and "The User Illusion". s
The UnConventional Wisdom -- Why (3z(BStuff(3y (BHappens -- Why Hits Happen -- Why wars, Economic Cycles, and Political Crises Happen -- Why Great Powers Come and Go -- Getting It Together -- Appendices.s
Keywords: Economics; Science (General).; Economics/Management Science; Economics/Management Science, general; Popular Science, general